COUNTERING TERRORISM CRIMES THROUGH SOFT APPROACHES AND HARD APPROACHES THAT OCCUR IN THE ACEH REGION - Zulfahmi Zulfahmi; Mukidi Mukidi; Panca Sarjana Putra (LPPM YPITI, 2025)
Terrorism is a type of crime that cannot be classified as an ordinary crime. The development of former terrorism prisoners, or what is often called former terrorism convicts (ex-prisoners), is a systematic effort to return them to society. This includes rehabilitation, social reintegration, and deradicalization to prevent them from being exposed to radical ideas and committing acts of terrorism. The development of former terrorism prisoners, or what is often called former terrorism convicts (ex-prisoners), is a systematic effort to return them to society. This includes rehabilitation, social reintegration, and deradicalization to prevent them from being exposed to radical ideas and committing acts of terrorism.